Pengalaman Keluarga dalam Perawatan Anak di Rumah Sakit Perbatasan: Studi Fenomenologi di Garis Batas Negara - Nurman Hidaya; Sulidah; M. Akbar Nugraha; Najihah; Nur Fadila (Window of Nursing Journal, 2026)
Sebatik is an island in the Nunukan district of North Kalimantan Province. Sebatik Island is owned by 2 countries, namely Indonesia and Malaysia. Sebatik has a primary hospital and is far from several villages. This study aims to explore the experiences of paediatric patients and their families when receiving health services at border hospitals. Methods: Qualitative content analysis was conducted using data collected through observation, in-depth interviews, and field notes in the hospital environment. A total of 6 informants were selected purposively from patient families. Results: This study identified three main themes that reflect the satisfaction of paediatric patients and their families when treated at border hospitals, including 1. Implementation of family-centred care through communication and education 2. Quality of medical services and 3. Availability and completeness of facilities. Conclusion: This study highlights the experiences of paediatric patients and their families when treated at border hospitals, amidst limited human resources (HR) and health service facilities. This study emphasises the importance of HR, facilities, equipment, and access to health services in border areas.